The Trends for Potential Development of Thai Processed Foods by The Behavior of The Chinese Customers to Develop The Marketing Strategies to Jinghong / แนวทางพัฒนาศักยภาพสินค้าอาหารแปรรูปไทยตามพฤติกรรมของกลุ่มลูกค้าสาธารณรัฐประชาชนจีนเพื่อพัฒนากลยุทธ์ตลาด - Pakvipas / รัฐนันท์ พงศ์วิริทธิ์ธร และภาคภูมิ ภัควิภาส, Ratthanan Pongwiritthon and Paklphum (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 1 (2559): January - April 2016, 2016)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาพฤติกรรมการบริโภคของลักษณะอาหารแปรรูปไทยตามความต้องการลูกค้าสาธารณรัฐประชาชนจีน เพื่อกำหนดกลยุทธ์การขยายธุรกิจอาหารไทยในพื้นที่เป้าหมาย ประชากรและกลุ่มตัวอย่างเชิงปริมาณจากกลุ่มลูกค้าที่ได้ซื้อสินค้าอาหาร แปรรูปไทยในเมืองสิบสองปันนา (เชียงรุ่ง) และเชิงคุณภาพจากผู้ประกอบการธุรกิจจำหน่ายสินค้าอาหารแปรรูปไทยในเขตสิบสองปันนาและนครคุนหมิง ผู้บริหารสมาคม ซึ่งการรวบรวมข้อมูลเชิงปริมาณจากการใช้แบบสอบถามภาษาจีนและข้อมูลเชิงคุณภาพ การสัมภาษณ์แบบเจาะลึกเป็นรายบุคคล ผู้ประกอบการสาธารณรัฐประชาชนจีนที่จำหน่ายสินค้าอาหารแปรรูปไทย ผลการวิจัย พบว่า พฤติกรรมในการซื้อสินค้าแปรรูปไทยโดยเลือกรสชาติเผ็ดร้อน สถานที่การเลือกซื้อจากซุปเปอร์มาเก็ต ปัจจัยตัดสินใจเลือกซื้ออาหารแปรรูปไทย ได้แก่ ความสะอาด คุณค่าทางโภชนาการ ซึ่งเหตุผลที่ชอบอาหารแปรรูปไทย ได้แก่ อร่อย หอมหวาน และนุ่ม ชอบรสชาติ โดยจากการสัมภาษณ์ผู้ประกอบการเพื่อกำหนดแนวทางการพัฒนาศักยภาพอาหารแปรรูปไทยตามทัศนะกลุ่มลูกค้าสาธารณรัฐประชาชนจีน เพื่อพัฒนากลยุทธ์ตลาดสู่เชียงรุ่ง ควรมุ่งเน้น 1) การส่งเสริมกลยุทธ์ทางการตลาดต้องมุ่งเน้นการตลาดระดับบนและตลาดมวลชน โดยควรสร้างตราสินค้าให้เห็นความโดดเด่นและสื่อสารถึงคุณภาพและความปลอดภัยของสินค้าอาหารแปรรูป 2) การส่งเสริมการสร้างความแตกต่างด้านผลิตภัณฑ์ โดยต้องเลือกรสชาติอาหารแปรรูปไทยที่รสเผ็ดร้อน ความสะอาด คุณค่าทางโภชนาการ สินค้าหลากหลายขนาด 3) การส่งเสริมกลยุทธ์ทางด้านราคา ควรตั้งราคาขายอาหารแปรรูปไทย ควรต้องคำนึงถึงปัจจัยด้านการรับรู้ในคุณค่าของสินค้าต่อค่าใช้จ่ายที่ได้จ่ายกับประโยชน์ที่ได้รับ มีหลากหลายราคาตามปริมาณสินค้า 4) การส่งเสริมกลยุทธ์ด้านช่องทางการจัดจำหน่ายหรือสถานที่จำหน่ายควรมุ่งไปที่ส่งออกผ่านตัวแทนกระจายสินค้าเพื่ออำนวยความสะดวกแก่การขยายตลาดในพื้นที่เป้าหมาย และ 5) การส่งเสริมด้านผลิตภัณฑ์ต้องมีการออกแบบบรรจุภัณฑ์เพื่อการส่งเสริมการขาย ที่แตกต่างกันไป ได้แก่ การผูกสินค้าเข้าด้วยกันหรือขายเป็นกลุ่ม หรือการให้คำแนะนำในการปรุง ขายปริมาณมากในราคาต่อหน่วยที่ถูกลง   คำสำคัญ : ศักยภาพ  สินค้าอาหารแปรรูป  เชียงรุ่ง  พฤติกรรมผู้บริโภค   Abstract This research aims to study the customers’ behavior and the characteristics of Thai processed food according to Chinese customers' need in order to determine the strategy and extend Thai food business in the target area. The population of quantitative sampling is the group of customers who bought Thai processed food in the Xishuangbanna Dai Autonomous Prefecture (Jinghong). The population of qualitative sampling is the Jinghong and Kunming entrepreneurs who sell Thai processed foods. The quantitative data were collected by using questionnaires in Chinese language while the qualitative data were collected by conducting an in-depth interview with Chinese entrepreneurs who sell Thai processed food. The research results that showed that the customers chose Thai processed food due to its hot and spicy taste and most commonly buy from supermarkets. The factors to decide to buy Thai processed food include cleanliness and nutrition. The reasons that consumers like Thai processed food are: Thai processed food are delicious, good flavor and delicate taste. From the interview with the entrepreneurs, the trends for potential development of Thai processed foods by the behavior of the Chinese customers in Jinghong should focus on the following: 1) A marketing strategy on the high-end market and mass market by creating a distinctive brand and communicating about the quality and safety of processed food products, 2) There should be the differences between each product and they should offer different product sizes, while still keeping the products clean, hot and spicy, and good nutrition, 3) The price of a product should be considered by the factor of perceived value of the product cost that the customer will pay and the benefits customer will get, 4) Place of distribution should aim to send out via distribution agents to facilitate the market expansion in the target area, and 5) Promotion and packaging design should provide different choices such as binding products together or sell set of products, or providing instruction on how to cook, and sell more volumes to lower down the price per unit.   Keywords: Potential, Processed Food Product, Jinghong, Customers’ Behavior
Keywords: แนวทางพัฒนาศักยภาพสินค้าอาหารแปรรูปไทย ตามพฤติกรรมของกลุ่มลูกค้าสาธารณรัฐประชาชนจีน เพื่อพัฒนากลยุทธ์ตลาดสู่เชียงรุ่ง ศักยภาพ สินค้าอาหารแปรรูป เชียงรุ่ง พฤติกรรมผู้บริโภค Potential, Processed Food Product, Jinghong, Customers’ Behavior